A questionnaire study of injections prescribed and dispensed for patients diagnosed with mild/moderate community-acquired pneumonia in Mongolia - Dorj, G.; Hendrie, D.; Parsons, Richard; Sunderland, B. (2015)
Purpose. The study aimed to determine the extent of and factors influencing the prescribing of injections for the treatment of mild/moderate community acquired pneumonia (CAP) in Mongolia. Methods. Questionnaires were developed and administered to medication providers (34 Pharmacists, 27 pharmacy technicians) and prescribers (22 general doctors and 49 medical specialists) working in Mongolia. Results. Cefalosporins were prescribed for patients with mild pneumonia and doctors tended to prescribe injectable cefalosporins (cefazolin) rather than oral dosage forms. This was supported by the questionnaire study with pharmacists and pharmacy technicians. Additionally, 23 pharmacists and pharmacy technicians indicated that OTC injectable cefalosporins (37.7%) and injectable aminopenicillins (33,9%) were frequently sold by pharmacies for the treatment of mild/moderate CAP. Doctors and particularly pharmacists in the questionnaire studies indicated choosing an injection was to avoid non-compliance problems. Conclusion. High levels of injectable prescribing of antibiotics were found in non-hospitalized patients with CAP in Mongolia. This prevalence level indicated that inappropriate injection prescribing is a public health hazard for Mongolia and requires consideration by the appropriate authorities.